The once and future king - White, T. H. (Terence Hanbury), 1906-1964. (New York : Ace, 1987)
Tells the story of the youth and reign of King Arthur, the establishment of the Round Table, and the search for the Holy Grail.
Young Adult
Young Adult
Wilson's Senior High School
Wilson's Junior High School
Wilson's Fiction
1080
Keywords: Arthur, -- King -- Fiction; Knights and knighthood -- Great Britain -- Fiction; Britons -- Kings and rulers -- Fiction; Arthurian romances -- Adaptations; Arthur, -- King -- Fiction; Knights and knighthood -- Fiction; Great Britain -- Kings and rulers -- Fiction; Arthurian romances -- Adaptations